Interactive Human-Centric Bias Mitigation - Vejsbjerg, Inge; Daly, Elizabeth M.; Nair, Rahul; Nizhnichenkov, Svetoslav (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Bias mitigation algorithms differ in their definition of bias and how they go about achieving that objective. Bias mitigation algorithms impact different cohorts differently and allowing end users and data scientists to understand the impact of these differences in order to make informed choices is a relatively unexplored domain. This demonstration presents an interactive bias mitigation pipeline that allows users to understand the cohorts impacted by their algorithm choice and provide feedback in order to provide a bias mitigated pipeline that most aligns with their goals.